Comparative Assessment of Procion Red Removal Using Magnetite-Based Composites with Humic Acid, Activated Charcoal, and Lignin - Nur Ahmad; Alfan Wijaya; Amri (Magister Program of Material Science Graduate School of Universitas Sriwijaya, 2025)
This investigation presents the synthesis and comparative assessment of three magnetite-based composite adsorbents, including Magnetite Humic Acid (MA), Magnetite Activated Charcoal (MB), and Magnetite Lignin (MC), aimed to remove Procion Red (PR) from aqueous solutions. The characterization of the materials was conducted through XRD, BET, and FTIR analyses, which validated the successful synthesis of magnetite and its interactions with the respective organic components. The point of zero charge (pHpzc) values obtained were 4.75, 5.09, and 4.10 for MA, MB, and MC, respectively. Adsorption experiments were performed under these pHpzc conditions to mitigate electrostatic influences. Kinetic investigations demonstrated that the adsorption process adhered to a pseudo-second-order model, signifying that chemisorption was the prevailing mechanism. Furthermore, the Langmuir isotherm yielded the most accurate representation of the equilibrium data, implying the occurrence of monolayer adsorption. MB demonstrated the highest adsorption capacity of PR, recorded at 52.632 mg/g at a temperature of 50oC. This observation underscores the benefits associated with its elevated surface area and the effective dispersion of Fe3O4 particles within the activated carbon matrix. The comparative analysis elucidates the impact of organic matrix selection on surface characteristics, interaction dynamics, and the overall efficacy of adsorption processes. This study presents novel findings regarding the development of natural carbon-magnetite composites aimed at enhancing the efficiency of dye removal processes.